(untitled) (Journal of Informatics Education and Research, 2024)
Technological innovations have created entrepreneurial opportunities worldwide and India with its burgeoning tech ecosystem is riding this wave. In the recent years technology - fueled Indian startup ecosystem has grown enormous. Disruptive technologies like artificial intelligence, blockchain, internet of things, machine learning etc also disrupted conventional industries creating new entrepreneurial undertakings across all industries. Similarly, democratization of tech has opened doors for diverse entrepreneurs to use cutting edge tools &; platforms to realise their ideas. Smartphones and cheap internet access have created these entrepreneurial opportunities &; opened businesses to a larger consumer base. In addition, government initiatives like Startup India and conducive policies have provided support for innovation and entrepreneurship through funding, mentorship and regulation. Stakeholders can push technological advancements and create growth of entrepreneurship in India through synergy and knowledge exchange. A sample of 249 respondents was collected from entrepreneurs of India. The variables that identify the role of technology innovations in Providing Cutting Edge- Entrepreneurial Opportunities in India are Digital Transformation, E-Commerce and Marketplaces, Artificial Intelligence and Machine Learning, and Internet of Things (IoT).